Factor 4n4 + n3.
A)n(4n3+ 1)
B)n3(4n + 1)
C)n3(4n)

Question

Asked 9/21/2012 11:23:34 AM

Updated 9/21/2012 2:52:57 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca

s

LoveSolo|Points 80|

austincarlisle|Points 35|

Expert answered|Pinkblush|Points 1|

Question

Asked 9/21/2012 11:23:34 AM

Updated 9/21/2012 2:52:57 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca

Rating

3

The factors of (x^4y^2 + x^3y^3 are: C. x^3y^2(x + y)

Added 9/21/2012 2:52:57 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/13/2014 3:09:31 PM]

factormr + ns - nr - ms User: factor mr + ns - nr - ms **Weegy:** mr + ns - nr - ms
bring similar terms together
mr - ms - nr + ns
take out similar factors in each pair of terms
m(r - s) -n (r - s)
(m - n) (r - s) **User:** Factor x2 + xy - 2x - 2y.
(x + 2)(x - y)
(x + y)(x - 2)
(x - y)(x + 2) **Weegy:** b.(x - y)(x + 2)
**User:** factor ab + 2a + 3b + 6 **Weegy:** (a+3)(b+2) **User:** factor mn - 4m - 5n + 20 **Weegy:** mn - 4m - 5n + 20
= (m-5) (n-4) **User:** Factor ab + bc + b2 + ac.
b(a + b)(b + c)
(a + c)(b + c)
(a + b)(b + c) **Weegy:** (a + b)(b + c). is the factor of ab + bc + b2 + ac **User:** Factor z3 - 2z2 + 9z - 18.
(z2+ 9)(z - 2)
(z2+ 2)(z - 9)
(z2- 9)(z - 2) **User:** Factor n3 - n2 + 3n - 3.
(n2- 3)(n - 1)
(n2+ 3)(n - 1)
(n2+ 1)(n - 3) **User:** Factor y2 + 10z - 10y - yz.
(z - y)(y - 10)
(y - z)(y - 10)
(y - z)(10 - y) **Weegy:** y^2 + 10z - 10y - yz is factored into 2. (y - z)(y - 10) **User:** Factor jm + jn + km + kn.
(j + k)(m + n)
(j + m)(n + k)
(n + j)(k + m) **Weegy:** jm + jn + km + kn = j(m + n) + k(m + n) =(j + k)(m + n) so your answer is 1.(j + k)(m + n) .Thank you and have a nice day ahead you
**User:** factor ab + 4 + a + 4b **User:** Factor the trinomial to find the length and width of the rectangle.
l = x + 6; w = x + 2
l = x + 5; w = x + 7
l = x + 4; w = x + 3 (More)

Question

Updated 9/21/2014 5:50:43 AM

2 Answers/Comments

x^2 + xy - 2x - 2y

=x(x + y) -2 (x+y)

=(x + y)( x - 2 )

=x(x + y) -2 (x+y)

=(x + y)( x - 2 )

Added 9/21/2014 5:44:20 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [9/21/2014 2:33:30 PM]

ab + 4 + a + 4b

= a(b + 1) + 4(1 + b)

= (b +1) (a + 4)

= a(b + 1) + 4(1 + b)

= (b +1) (a + 4)

Added 9/21/2014 5:49:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [9/21/2014 2:31:35 PM]

What is the product of (n - 8)(n + 2)?
n2- 10n - 16
n2+ 10n - 16
n2+ 6n - 16
n2- 6n - 16 **Weegy:** 3x 2 - x - 15x + 5 = x(3x - 1) - 5(3x -1) = (3x ... [ factors are (x + 0.7863) and (x - 2.11963) How do you factor 3x squared minus 3x minus 60? 3x2 - 3x - 60 = 3(x2 - x - 20) = 3 ... [ ] ] **User:** Factor y2 + 5y + 6.
(y + 1)(y + 6)
(y + 2)(y + 3)
(y + 2)(y + 4) **User:** Factor y2 + 5y + 6. **Weegy:** 6(5+y) **User:** What is the middle term of the product of (x - 4)(x - 3)? **User:** ya know weegy you really are stupid **Weegy:** Weegy is sorry you feel that way. How can we help you? **User:** by answering my dang questions right **User:** how much herb should i get for 5 dollars (More)

Question

Updated 6/24/2014 2:33:58 PM

3 Answers/Comments

(n - 8)(n + 2) = n^2 + 2n - 8n - 16 = n^2 - 6n - 16

Added 6/24/2014 2:33:33 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/24/2014 2:39:45 PM]

y^2 + 5y + 6 = (y + 2)(y + 3)

Added 6/24/2014 2:33:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/24/2014 2:39:41 PM]

What is the product of (-a + 3)(a + 4)? **Weegy:** (-a + 3)(a + 4)
= -a^2 -a + 12 **User:** What is the middle term of the product of (x + 5)(x + 2)? **User:** What is the middle term of the product of (x + 5)(x + 2)?
A)7x
B)10x
C)18x **Weegy:** 7x **User:** factor a2 - a - 20 **User:** Factor p2 + 18p + 32.
(p + 4)(p + 8)
(p + 2)(p + 16)
(p + 16)2 **Weegy:** b.(p + 2)(p + 16)
to check:
p*p + (2p + 16p) + (2 * 16)
= p^2 + 18p + 32
so the answer is b.(p + 2)(p + 16)
**User:** Factor x2 + 29x - 30.
(x + 15)(x - 2)
(x + 1)(x - 30)
(x - 1)(x + 30) **Weegy:** x+3)(x-3) = x2+3x-3x -9 = x2-9 **User:** Factor x2 + 29x - 30.
A)(x + 15)(x - 2)
B)(x + 1)(x - 30)
C)(x - 1)(x + 30) **Weegy:** x+3)(x-3) = x2+3x-3x -9 = x2-9 **User:** What is the product of (n - 8)(n + 2)?
A)n2- 10n - 16
B)n2+ 10n - 16
C)n2+ 6n - 16
D)n2- 6n - 16 **Weegy:** 3x 2 - x - 15x + 5 = x(3x - 1) - 5(3x -1) = (3x ... [ factors are (x + 0.7863) and (x - 2.11963) How do you factor 3x squared minus 3x minus 60? 3x2 - 3x - 60 = 3(x2 - x - 20) = 3 ... [ ] ] (More)

Question

Updated 12/18/2014 5:27:29 AM

2 Answers/Comments

x^2 + 29x - 30

= x*x + 30x - x + 30*(-1)

= (x + 30)(x - 1)

= x*x + 30x - x + 30*(-1)

= (x + 30)(x - 1)

Added 12/18/2014 5:26:56 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [12/18/2014 5:42:55 AM]

(n - 8)(n + 2)

= n*n - 8n + 2n - 8*2

= n^2 - 6n - 16

= n*n - 8n + 2n - 8*2

= n^2 - 6n - 16

Added 12/18/2014 5:27:29 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [12/18/2014 5:44:34 AM]

31,997,731

questions answered

There are no comments.